A Study of Radiation Protection Standards Compliance in Hospital Radiographic Departments in Iran - Nima Hamzian; Saeed Asadian; Hassan Zarghani (Journal of Biomedical Physics and Engineering, 2022)
Background: The X-ray is a critical diagnostic and therapeutic tool with harmful effects. The International Commission on Radiological Protection (ICRP) has some recommendations regarding applying radiation protection principles.Objective: This study aimed to determine the standards of the typical radiation protection in radiographic departments of hospitals in Iran.Material and Methods: In this cross-sectional descriptive study, the usual radiation protection standards in places, such as the physical environment of the control and waiting rooms, radiographic devices, the physical space of the darkroom, and shielding facilities, were investigated using a checklist in Iran. A total of 84 hospitals in 51 cities throughout Iran were randomly selected, and the checklists were distributed to the radiation protection officers. In hospitals with multiple radiography rooms, the radiation protection officers were asked to complete the checklist about the room with the highest workload as a baseline to evaluate their facilities. Finally, the authors reviewed all checklists.Results: In radiology departments in control and waiting rooms, the mean of radiation protection was 71.9%. Pregnancy and radiation warning signs and labels were present in 96.1% of the parameters, while gonad shielding protocols were not presented. Conclusion: The principles of observed radiation protection were unsatisfactory, and it is recommended that surveillance be conducted at frequent intervals.